Diversity of mental illnesses in the history of social media in the 21st century - Bálint Emma Júlia („RIK-U” Kft., 2018)
Abstract. In today’s world, more and more people feel like sharing their problems online; therefore, mental illnesses are gaining a much greater degree of attention, than ever before. Individuals have multiple virtual platforms to share their problems on nowadays, such as Twitter, Facebook, Tumblr, or Instagram – just to name a few.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: 21st century; social media; mental illnesses